Vestibular Injury After Low-Intensity Blast Exposure - Lien, Steven; Dickman, J. David (Frontiers in Neurology, 2018)
The increased use of close range explosives has led to a higher incidence of exposure to blast-related head trauma. Exposure to primary blast waves is a significant cause of morbidity and mortality. Active service members and civilians who have experienced blast waves report high rates of vestibular dysfunction, such as vertigo, oscillopsia, imbalance, and dizziness. Accumulating evidence suggests that exposure to blast wave trauma produces damage to both the peripheral and central vestibular system; similar to previous findings that blast exposure results in damage to auditory receptors. In the present study, mice were exposed to a 63 kPa peak blast-wave over pressure and were examined for vestibular receptor damage as well as behavioral assays to identify vestibular dysfunction. We observed perforations to the tympanic membrane in all blast animals. We also observed significant loss of stereocilia on hair cells in the cristae and maculae up to 1 month after blast-wave exposure; damage that is likely permanent. Significant reductions in the ability to perform the righting reflex and balance on a rotating rod that lasted several weeks after blast exposure were prominent behavioral effects. We also observed a significant reduction in hVOR gain and phase lags in the eye movement responses that lasted many weeks following a single blast exposure event. OKN responses were absent immediately following blast exposure, but began to return after several weeks recovery. These results show that blast-wave exposure can lead to peripheral vestibular damage (possibly central deficits as well) and provides some insight into causes of vestibular dysfunction in blast-trauma victims.